Cell volume regulation following hypotonic stress in the intestine of the eel, Anguilla anguilla, is Ca2+-dependent - TRISCHITTA, Francesca Ross; DENARO, Maria Gabr.; FAGGIO, Caterina (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2005)
The involvement of Ca2+ in the regulatory volume decrease (RVD) mechanism was studied in both isolated enterocytes and intestine of the eel, Anguilla anguilla. Videometric methods and electrophysiological techniques were respectively employed. The isolated enterocytes rapidly swelled following a change from isotonic (315 mOsm/kg) to hypotonic (180 mOsm/kg) saline solutions. Afterwards, they tended to recover their original size. This homeostatic response was inhibited both in the absence of extracellular Ca2+ and in the presence of TMB8, an inhibitor of Ca2+ release from intracellular stores. It is likely that Ca2+ entry through verapamil-sensitive Ca2+ channels is responsible for RVD since the blocker impaired the ability of the cell to recover its volume after the hypotonic shock. The observation that a 10-fold increase of K+ concentration as well as the presence of quinine in the hypotonic solution completely abolished RVD indicated the involvement of K+ in this response. Experiments performed with the isolated intestine suggested that the opening of basolateral K+ channels facilitates K+ loss (and hence water efflux) from the cell during RVD and that this opening is probably due to Ca2+ entry into the cell through both the mucosal and the serosal membranes.